Олександр Андрійович Шостак – одеський поліцмейстер (1839–1841 pp.), наказний отаман Дунайського козацького війська (1847–1854 pp.), військовий комендант Одеси (1854–1868 pp.) - Хромов, А. (Чорноморська минувшина, 2014)
У статті на основі архівних та друкованих матеріалів висвітлені основні факти з життя Олександра Шостака – одеського поліцмейстера, наказного отамана Дунайського козацького війська, військового коменданта Одеси. On the basis of archival and printed materials highlight the basic facts of the life of Alexandra Shostak - Odesa police chief, otaman of the Danube Cossack troops, the military commandant of Odesa. It is proved that Alexander Shostak was a member of one of the famous Ukrainian Cossack families. Representatives of the family held high positions in the south of Ukraine in the 19th century. Probably his father was Andrew Shostak - Vice Governor Taurida Gubernia. Some of his brothers as well as he received the rank of general and served as Chief of Police of cities of the southern provinces of the Russian Empire. Olexander Shostak implement a successful military and civilian careers. In memory of the people, he is known as a liberal and a bit eccentric Odessa police, Ataman of Danube Cossack Host, Military Commandant of Odessa. The article made an analysis of its activities in these positions. Describe his achievements and failures. Referred to his actions in the field of philanthropy. For many years he was the director of the Odesa Committee on Trusteeship prisons. Provide a brief biographical information about his sons. В статье на основе архивных и печатных материалов освещены основные факты из жизни Александра Шостака - одесского полицмейстера, наказного атамана Дунайского казацкого войска, военного коменданта Одессы.